DAMPAK HUKUM KETENAGAKERJAAN PASCA OMNIBUS LAW DILANJUT PASCA PUTUSAN MK NO. 168/PUU-XXI/2023 TERHADAP PEKERJA - Aswanti, Wiwik; Damono, Hari; Sarino, Sarino; Indrayana, Mohamat; Purdiyanto, Heru; Antoko, Noto (Gapenas Publisher, 2025)
Labor laws play an important role in ensuring legal certainty and a balance of rights and obligations between workers and employers. However, the enactment of the Job Creation Law (Omnibus Law) has sparked controversy because it is considered to accommodate the interests of employers and investors more than those of workers. This study examines the impact of the Job Creation Law and Constitutional Court Decision No. 168/PUU-XXI/2023 on the conditions of workers and industrial relations in Indonesia. Using a normative legal research method, this paper highlights changes in aspects of worker protection, including termination of employment, wages, severance pay, outsourcing, and apprenticeships. On the other hand, the role of labor unions as a means of fighting for workers' rights faces strategic challenges that encourage their involvement in the political arena. The results of the analysis show that the implementation of the Omnibus Law has created legal uncertainty and weakened the bargaining position of workers. Therefore, more equitable and inclusive labor regulations are needed, which are not drafted using the omnibus method. In conclusion, ideal labor laws must be able to create harmonious and equitable industrial relations for the welfare of workers, business sustainability, and social stability.